2009
DOI: 10.1074/jbc.m109.052415
|View full text |Cite
|
Sign up to set email alerts
|

Two Pathways for Cyclooxygenase-2 Protein Degradation in Vivo

Abstract: COX-2, formally known as prostaglandin endoperoxide H synthase-2 (PGHS-2), catalyzes the committed step in prostaglandin biosynthesis. COX-2 is induced during inflammation and is overexpressed in colon cancer. In vitro, an 18-amino acid segment, residues 595-612, immediately upstream of the C-terminal endoplasmic reticulum targeting sequence is required for N-glycosylation of Asn 594 , which permits COX-2 protein to enter the endoplasmic reticulum-associated protein degradation system. To determine the importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…PGHS-1 and PGHS-2 have three common N-glycosylation sites at Asn-68, Asn-144 and Asn-410 25-30 that appear to be glycosylated co-translationally 30,31 (Figures 2 and 3). NMR and mass spectral analyses of the carbohydrate chains of PGHSs indicate that the structures of the N-glycosyl moieties are of the form (Man) n (GlcNAc) 2 (n = 6-9) 32-34 .…”
Section: Prostaglandin Endoperoxide H Synthases (Pghss)mentioning
confidence: 99%
“…PGHS-1 and PGHS-2 have three common N-glycosylation sites at Asn-68, Asn-144 and Asn-410 25-30 that appear to be glycosylated co-translationally 30,31 (Figures 2 and 3). NMR and mass spectral analyses of the carbohydrate chains of PGHSs indicate that the structures of the N-glycosyl moieties are of the form (Man) n (GlcNAc) 2 (n = 6-9) 32-34 .…”
Section: Prostaglandin Endoperoxide H Synthases (Pghss)mentioning
confidence: 99%
“…N-Glycosylation of Asn594 leads to entry of COX-2 into the endoplasmic reticulum-associated degradation pathway. The second COX-2 degradation process is substrate turnover dependent and is independent of N-glycosylation at Asn594 (Wada et al, 2009). Notably, COX-2 protein stability has been found to be enhanced by atorvastatin, which may influence dendritic cell (DC) function and counteract some of the untoward effects associated with sustained inhibition of COX-2 (Alvarez et al, 2009b).…”
Section: Cox Enzymes and Cox/lipoxygenasementioning
confidence: 99%
“…Finally, with respect to degradation, we note that in addition to ERAD COX-2 is subject to substrate turnover-induced degradation (29,30). This latter process does not require N-glycosylation of Asn-594.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
“…We have reported that properly folded COX-2 can be degraded via two distinct pathways including AA turnover-dependent degradation and constitutive degradation involving the ER-associated degradation (ERAD) pathway (29,30). Others have shown that COX-2 can be ubiquitinated and degraded through the 26 S proteasome (32,35).…”
mentioning
confidence: 99%
See 1 more Smart Citation